3D Printing Properties of Surimi Inks Modulated by Bigels - WU Jiajie, TIAN Han, ZHONG Changxiu, CAI Xixi, HUANG Jianlian, WAN Shuo, CHEN Xu, WANG Shaoyun (Shipin Kexue)
The aim of this study was to investigate the effects of the composition of bigels on rheological performance, 3D printing performance and textural properties of surimi inks. The results showed that when the addition level of beeswax was 9.0%, the mass ratio of oleogel (9% beeswax) to hydrogel (4% xanthan gum) was 6:4, and the mass ratio of bigels to surimi was 3:7, the moisture content of surimi was 86%, the best rheological properties were obtained with yield stress (τ0) of 44.44 Pa, viscosity index (K) value of 7.972 × 104 Pa⋅sn, flow index (n) value of 0.265, and recovery rate of 86.75%. The surimi inks with bigels were able to continuously print up to 40 layers of 20.00 mm × 20.00 mm × 40.00 mm rectangular structures and some types of complex structures. And the printed structures had a hardness of 204.91 g, elasticity of 0.28, cohesiveness of 0.26, adhesiveness of 52.68 g, and breaking strength of 31.65 g. This study provides ideas for the development and application of bigels in food 3D printing.